Topical problems of nonlinear plastic deformation and fracture dynamics; Physical Mesomechanics; Vol. 14, iss. 5-6, Sept.-Dec. - Panin V. E. Viktor Evgenyevich (2011, 2011)
В фонде НТБ ТПУ отсутствует